Y-chromosomal diversity in the population of Guinea-Bissau: a multiethnic perspective - Rosa, Alexandra (2020)
The geographic and ethnolinguistic differentiation of many African Y-chromosomal lineages provides an opportunity to evaluate human migration episodes and admixture processes, in a pan-continental context. The analysis of the paternal genetic structure of Equatorial West Africans carried out to date leaves their origins and relationships unclear, and raises questions about the existence of major demographic phenomena analogous to the large-scale Bantu expansions. To address this, we have analysed the variation of 31 binary and 11 microsatellite markers on the non-recombining portion of the Y chromosome in Guinea-Bissau samples of diverse ethnic affiliations, some not studied before.Results: The Guinea-Bissau Y chromosome pool is characterized by low haplogroup diversity (D = 0.470, sd 0.033), with the predominant haplogroup E3a*-M2 shared among the ethnic clusters and reaching a maximum of 82.2% in the Mandenka people. The Felupe-Djola and Papel groups exhibit the highest diversity of lineages and harbor the deep-rooting haplogroups A-M91, E2-M75 and E3*-PN2, typical of Sahel's more central and eastern areas. Their genetic distinction from other groups is statistically significant (P = 0.01) though not attributable to linguistic, geographic or religious criteria. Non sub-Saharan influences were associated with the presence of haplogroup R1b-P25 and particular lineages of E3b1-M78. Conclusion: The predominance and high diversity of haplogroup E3a*-M2 suggests a demographic expansion in the equatorial western fringe, possibly supported by a local agricultural center. The paternal pool of the Mandenka and Balanta displays evidence of a particularly marked population growth among the Guineans, possibly reflecting the demographic effects of the agriculturalist lifestyle and their putative relationship to the people that introduced early cultivation practices into West Africa. The paternal background of the Felupe-Djola and Papel ethnic groups suggests a better conserved ancestral pool deriving from East Africa, from where they have supposedly migrated in recent times. Despite the overall homogeneity in a multiethnic sample, which contrasts with their social structure, minor clusters suggest the imprints of multiple peoples at different timescales: traces of ancestral inhabitants in haplogroups AM91 and B-M60, today typical of hunter-gatherers; North African influence in E3b1-M78 Y chromosomes, probably due to trans-Saharan contacts; and R1b-P25 lineages reflecting European admixture via the North Atlantic slave trade.